Prognostic significance of dysregulation of shelterin complex and its correlation with telomere length and cytogenetics in multiple myeloma - Akanksha A. Kalal; Reshma A. Shetty; Akshay Bairapura Manjappa; Nagaraj V. Kulkarni; Prashanth Shetty (Journal of Genetic Engineering and Biotechnology, 2023)
Abstract Background MM (multiple myeloma) is a bone marrow disease with the accumulation of malignant plasma cells characterized by the neoplastic transformation of differentiated B cells. The onset and progression of cancer are greatly influenced by telomere dysfunction. We aimed to study the biomarker potential and prognostic significance of shelterin complex and hTERT. Telomere length and gene expression were measured using real-time quantitative reverse transcription-polymerase chain reaction (RT-qPCR), and these results were further correlated with clinical parameters. Results Our study showed increased expression of all genes in complex, hTERT, and TL in MM (n = 72) in comparison with controls (n = 31). TRF2 (P = 0.025) and hTERT (P = 0.0002) displayed significant association among cytogenetic analysis. The receiver operative curve showed POT1 and RAP1 with a greater area under the curve (AUC). RAP1 (P = 0.020) and hTERT (P = 0.037) displayed to be independent prognostic markers for overall survival. Clinical parameters and genes were observed to be significantly correlated. Conclusion Our study findings showed variation in telomere-associated genes and suggest the participation of these genes as prognostic markers in MM. These results all together highlight the evaluation and role of genes involved in telomeric alteration and TL, providing the opportunity to study new therapeutic approaches in patients with MM.